Management of haemothoraces in blunt thoracic trauma: study protocol for a randomised controlled trial. Issue 3 (3rd March 2018) - Carver, David A; Bressan, Alexsander K; Schieman, Colin; Grondin, Sean C; Kirkpatrick, Andrew W; Lall, Rohan; McBeth, Paul B; Dunham, Michael B; Ball, Chad G
Abstract : Introduction: Haemothorax following blunt thoracic trauma is a common source of morbidity and mortality. The optimal management of moderate to large haemothoraces has yet to be defined. Observational data have suggested that expectant management may be an appropriate strategy in stable patients. This study aims to compare the outcomes of patients with haemothoraces following blunt thoracic trauma treated with either chest drainage or expectant management. Methods and analysis: This is a single-centre, dual-arm randomised controlled trial. Patients presenting with a moderate to large sized haemothorax following blunt thoracic trauma will be assessed for eligibility. Eligible patients will then undergo an informed consent process followed by randomisation to either (1) chest drainage (tube thoracostomy) or (2) expectant management. These groups will be compared for the rate of additional thoracic interventions, major thoracic complications, length of stay and mortality. Ethics and dissemination: This study has been approved by the institution's research ethics board and registered with ClinicalTrials.gov. All eligible participants will provide informed consent prior to randomisation. The results of this study may provide guidance in an area where there remains significant variation between clinicians. The results of this study will be published in peer-reviewed journals and presented at national and international conferences. Trial registration number: NCT03050502 .